1991
DOI: 10.2527/1991.6941403x
|View full text |Cite
|
Sign up to set email alerts
|

Nulliparous versus primiparous crossbred females for beef.

Abstract: Feedlot and carcass traits of nulliparous and primiparous females representing eight breed types, including Bos taurus and Bos indicus x Bos taurus crosses, were evaluated. Nulliparous females (heifers) were in the feedlot for 4 mo; primiparous females (heiferettes) were fed for 2 1/3 mo after their calves were weaned at 6 mo of age. Heifers averaged higher (P less than .01) in dressing percentage, percentage of kidney fat, carcass grade (P less than .10), and color of lean (P less than .05) compared with heif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
1
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
3
4
1
1
Order By: Relevance
“…The similar ultimate meat pH values for the unbred, empty, and calved heifers in this study agree with the results of Bailey et al (1991) and Dumont et al (1987), but Vincent et al (1991) reported higher values for calved heifers.…”
Section: Meat Quality Characteristicssupporting
confidence: 89%
See 4 more Smart Citations
“…The similar ultimate meat pH values for the unbred, empty, and calved heifers in this study agree with the results of Bailey et al (1991) and Dumont et al (1987), but Vincent et al (1991) reported higher values for calved heifers.…”
Section: Meat Quality Characteristicssupporting
confidence: 89%
“…38 The absence of significant differences in weight-adjusted rib-eye area agrees with the results of Bailey et al (1991) and Waggoner et al (1990). The combined weight of six hind-quarter cuts, after being adjusted to a constant carcass weight, was slightly greater in calved heifers than in the other two breeding groups ( Table 2), suggesting that carcasses of calved heifers either had less fat or higher muscle to bone ratios.…”
supporting
confidence: 70%
See 3 more Smart Citations